POTENTIAL ROLE OF A PREDICTIVE BIOMARKER IN THE PROGRESSION OF FATTY LIVER DISEASE - Dinora A. Parpiboyeva; Nodirbek Sh. Ergashov; Muharram A. Musayeva; Xikmat Q. Boltaboyev (Central Asian Journal of Medicine, 2023)
Non-alcoholic fatty liver disease (NAFLD) is the most common liver disease in industrialized countries, affecting about 25.24% of the general population. NAFLD is a benign disease, but it can develop into more serious diseases, including non-alcoholic steatohepatitis (NASH), fibrosis, cirrhosis, and finally hepatocellular carcinoma (HCC). Liver biopsy is still the gold standard for diagnosing NAFLD. Due to the risks associated with liver biopsy and the inability to apply it on a large scale, it is now necessary to identify non-invasive biomarkers that can reliably identify patients at increased risk of progression. Thus, in this review, we report on biomarkers used in clinical practice for diagnosing NASH as well as for staging fibrosis, and secondly, we draw attention to new biomarkers, miRNAs, long non-coding RNAs, for diagnosing and staging fibrosis. This review discusses the potential role of miRNAs in the pathogenesis of fatty liver disease.